Extensive cytonuclear discordance in a crested newt from the Balkan Peninsula glacial refugium. (28th May 2020) - Wielstra, Ben; Arntzen, Jan W
Abstract: Integration of multilocus data and species distribution modelling into phylogeography allows mitochondrial DNA (mtDNA)-based scenarios to be fine-tuned. We address the question of whether extensive mtDNA substructuring in the crested newt Triturus macedonicus from the Balkan Peninsula is matched in the nuclear genome. We determine the intraspecific population structure based on 52 nuclear DNA markers and project a species distribution model on climate layers for the Last Glacial Maximum. We show that T. macedonicus accumulated nuclear DNA population structure in an area predicted to have been climatically stable during the Pleistocene, with four nuclear DNA groups in the western part of the species range. The distribution of these nuclear DNA groups shows little agreement with that of mtDNA structuring, which shows three highly distinct species-specific clades and a fourth one introgressed from another crested newt species. This cytonuclear discordance conveys that historical biogeographical scenarios based on mtDNA exclusively should be interpreted with caution. Our findings further highlight the important role the Balkan Peninsula has played in the evolution and preservation of European biodiversity.